POTENSI BAHAN ALAM BAWAH LAUT SEBAGAI OBAT ALAMI UNTUK PENGOBATAN DIABETES - Agustina, Putri (Politeknik Tiara Bunda, 2024)
The potential of underwater natural materials has attracted the attention of researchers and health professionals as an effective source of natural remedies for the treatment of diabetes. Several examples of polyphenol compounds found in underwater natural materials have the ability to act as antioxidants, so they are widely used to improve the condition of diabetic patients. Polyphenols have the ability to suppress postprandial hyperglycemia by inhibiting the hydrolysis activity of enzyme carbohydrates, inhibiting glucose transport in the blood, affecting the function of cells β pancreas, and glucose absorption tissue. The method used in this writing is literature review using international and national journals that are in accordance with the purpose of writing. Thus, the potential of underwater natural ingredients as a natural remedy for diabetes treatment is very promising and needs to be further examined and developed to improve the quality of life of diabetics.